A socio-spatial rhetorical analysis of The ruins of Detroit - Stricker, Sarah Teresa, author; Dickinson, Greg, advisor; Dunn, Thomas, committee member; MacDonald, Bradley, committee member (Colorado State University. Libraries, 2015)
The Ruins of Detroit is a bound collection of recent photographs by Yves Marchand and Romain Meffre of decaying architecture and infrastructure in Detroit, Michigan. This thesis finds that the experience of reading The Ruins of Detroit constitutes the reader as a post-Fordist colonist, and in turn constitutes Detroit as a post-Fordist frontier. Informed by Foucauldian historical understanding and Edward Soja's argument for the foregrounding of critical spatial studies, I first discuss the history of Detroit to demonstrate how spatial practices in Detroit have influenced the enabling or disabling of human bodies in the city. These events are characterized within definitions of Fordism and post-Fordism. Secondly, I detail the relationship between ruins and the body within Western art history. I find that ruins in art echo human understandings of our bodies in relation to materials. Looking at art pieces as diverse as Andrea Mantegna's Saint Sebastian (1480) and Robert Smithson's Spiral Jetty (1970), ruins prove to be places of dissection. Contemporary representations significantly merge the body with ruins, and ruins with the body. Thirdly, I point out symbols in the text that construct the reader as a post-Fordist colonist of Detroit. Using Richard Slotkin's critiques of the frontier myth as a model, I find that the interaction between reader and Ruins recycles the myth of the frontier in several ways. By acknowledging some of the failures of capitalist development, such as the prevalence of waste, the spaces within The Ruins critique the legitimacy of formerly organized institutions. Yet The Ruins simultaneously gives entitled access to resources within Detroit, encouraging adaptive use and re-use. The privilege and expressed availability produces an anxiety in the midst of the bodily presence of the indigenous population. This thesis enhances several perspectives for rhetorical studies. It argues that the frontier myth still holds rhetorical significance in the late capitalist era. The exploration serves as an example of a rhetorical analysis that accounts for the interrelatedness of subject and text. Within this understanding, it follows, and is used as a method in this study, that modes of production influence dwelling practices, a partly rhetorical action. Additionally, this thesis has political and philosophical implications concerning the nature of dwelling practices in the twenty-first century. For instance, this thesis suggests that the violence of imperialism continues to influence a post-Fordist era. In sum, this study seeks to infuse a rhetorical analysis with critical geography, inspired by Thomas Rickert, Jane Bennett, and Debra Hawhee, among others, who point out that rhetoric is intertwined with spatial and bodily practices of dwelling and an ecological relationship with materials.
Keywords: ruins; Detroit